PERAN BMT NUSANTARA DALAM PEMBERDAYAAN USAHA MIKRO KECIL MENENGAH (UMKM) DI SITUBONDO - Sufyanto, Budi; Hoirul Anam, Mohamad (Wasīlah: Journal Of Sharia Sciences, 2026)
Baitul Maal wat Tamwil (BMT) contributes significantly to the development of MSMEs (Micro, Small, and Medium Enterprises) in East Java, particularly in the Situbondo Regency, by providing business capital financing (barakah business capital) and entrepreneurship training. Consequently, this increases the productivity and competitiveness of micro, small, and medium enterprise actors. This study analyzes the extent to which BMT's programs and activities aim to improve MSMEs, as well as the influence of Sharia financing on MSME growth. The findings indicate that a Sharia-based approach not only fulfills financial needs but also strengthens the economic inclusion of the ummah (community), despite existing challenges such as the risk of default. The results emphasize the necessity for synergy between BMT, the government, and MSMEs to optimize these impacts. This research utilizes a descriptive qualitative method, employing data collection techniques through observation, documentation, and interviews. The study was conducted in the Situbondo Regency. The research subjects include BMT Nusantara, regarding its operations, and the MSMEs fostered through capital provision, additional capital, and mentoring provided by BMT.